The Effect of Money Supply and Interest Rates on the Value of Inflation in North Sumatra - Tirtana, Muhammad Arief (Politeknik Negeri Bengkalis, 2024)
Inflation is an increase in the price of an item that occurs continuously. This study aims to determine the effect of money supply and interest rates on inflation in Indonesia for the period 2016-2022. The type of data in this study is secondary data obtained from the Central Bureau of Statistics. Based on the results of hypothesis testing with the Multiple linear Regression Model shows that the money supply variable has a positive and insignificant effect on the inflation rate in Indonesia, while the interest rate variable has a positive and significant effect on inflation as indicated by a probability value of 0.0046 smaller than alpha 0.005. Related to the results of this can be due to the policies and strategies implemented by the government the government is still in a less effective condition to suppress existing inflation, so the government should be more relevant in making policies so that inflation does not continue to decline and even become a deficit that has an impact on economic stability in Indonesia. Therefore, the government needs to implement monetary policy carefully so that the economy in Indonesia is stable.Keywords: Â Inflation, Money Supply, Interest Rate